Hakikat Manusia Menurut Pandangan Islam dan Kristen - Miranda, Setia; Kamaluddin, Kamaluddin; Fitriani, Fitriani (Lembaga Yasin AlSys, 2023)
This research examines human nature according to Islamic and Christian views. The research method used by researchers is a qualitative research method with a library research model because the data sources used are literature data. In this research the author uses a historical approach. The historical method in the general sense is the examination of a problem by applying a solution from a historical perspective. The results of this research show that by observing and responding to the previous description, the following conclusions can be drawn: Human Understanding. Humans are creatures created by God consisting of physical (body) and spiritual (soul) elements which cannot be separated. It is this body and soul that form an individual. humans are creatures who face themselves, but also face difficulties and so on. Humans are endowed with the power to exercise will and choose ways. In the view of believers, humans are noble and honorable creatures in the sight of God. Christianity and Islamic teachings both have a method of love, namely the undying human desire for what is true, good and beautiful. Humans will move towards good life attitudes and towards beautiful knowledge, from there finally to knowledge which is none other than the knowledge of supernatural beauty itself, in this way humans will finally know what is truly beautiful. Love will only be obtained by someone who has a good soul, a clean sheet, a pure heart and heart that is illuminated from within which points him towards the straight path. Beauty is an essential practice in the element of the soul. so that someone will come to the love of Allah.